1990
DOI: 10.1002/acp.2350040602
|View full text |Cite
|
Sign up to set email alerts
|

Learning implications of field dependence‐independence: Cognitive style versus cognitive ability

Abstract: The relationship between field dependence-independence and learning has been the subject of much research. In particular it has been suggested that matching teachers aKd students on cognitive style may produce beneficial results. Much research has also related cognitive style to the way students learn, the way teachers teach, and the way students make choices and perform in various academic areas. While cognitive style has provided the theoretical framework, it is found upon re-examination that a contrasting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
7

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 60 publications
1
17
0
7
Order By: Relevance
“…An optimist, though, might be impressed by the research effort that has gone into this topic, by the proliferation of ideas, and by the evidence already accumulated. Nevertheless, pessimists sound more profound than optirnists, and hence most recent reviewers in the field tend to be highly critical of developments in this area (Guilford, 1980;McKenna, 1990;Messick, 1984;Tiedemann, 1989).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…An optimist, though, might be impressed by the research effort that has gone into this topic, by the proliferation of ideas, and by the evidence already accumulated. Nevertheless, pessimists sound more profound than optirnists, and hence most recent reviewers in the field tend to be highly critical of developments in this area (Guilford, 1980;McKenna, 1990;Messick, 1984;Tiedemann, 1989).…”
Section: Resultsmentioning
confidence: 98%
“…McKenna (1990) noted that the concept of cognitive style has generated much research, particularly the way students learn; the way teachers learn; the concept of cognitive style matehing and the preferences of students for courses, teaching methods, and the like. But McKenna believes that the consistency with which research, for example, has shown field-independent individuals perform more effectively than field-dependent individuals contradicts the style conception and suggests a contrasting interpretation in terms of cognitive ability.…”
Section: Variance Accounted For Even If Styles Existmentioning
confidence: 98%
“…The other type of critique is deconstructive in the sense that attempts are made to undo or discount the style as a meaningful construct or to discredit its purported indicators as measures of something else entirely, such as intellective ability. Examples here are a series of critiques by McKenna (1983McKenna ( , 1984McKenna ( , 1990 and by Tiedemann (1989). McKenna (1984) reviews numerous studies demonstrating that EFT correlates substantially with measures of analytical intelligence, especially Wechsler's -25 -nonverbal index and Raven's progressive matrices.…”
Section: Ideowgy Of Constructive Versus Deconstructive Criticismsmentioning
confidence: 99%
“…For example, Witkin points out that "whereas field dependence-independence is a process variable, representing degree of autonomous functioning in assimilating information from self and field, locus of control is an attitudinal or belief variable, representing expectancies of internal or external control of reinforcement·' (Witkin & Goodenough, 1981, p. 48). McKenna (1990)"also examined many of the same educational studies of field independence that Davis (1991) reviewed. but he reinterpreted all of the findings in terms of ability differences rather than style differences.…”
Section: Ideowgy Of Constructive Versus Deconstructive Criticismsmentioning
confidence: 99%
“…As found with the use of the CSA, the scale used to measure field independence has been criticised. McKenna (1990) argued it is likely field independence is not measuring cognitive style but instead measures intellectual ability. In light of these criticisms, conclusions drawn from previous research involving these assessments of cognitive style are, at best, tentative.…”
mentioning
confidence: 98%